Kecerdasan Emosi Siswa Ditinjau dari Jenis Kelamin dan Jenjang Kelas - Khairul Bariyyah; Leny Latifah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
Emotional intelligence refers to the capability of a person to manage and control his or her emotions and possess the ability to control the emotions of others as well. Emotional intelligence is a very important skill for students. It is said to have five main elements such as self-awareness, self-regulation, motivation, empathy, and social skills. The purpose of this study First, to describe the level of emotional intelligence of junior high school students of Malang. Second, describe the differences of emotional intelligence based on gender and grade level. This research method is quantitative descriptive. The research sample was 313 students of State Junior High Schools in Malang selected by cluster random sampling technique. The research instrument used a scale of emotional intelligence consisting of 48 items, data analysis using descriptive analysis and T-test. The results showed 1) 25.9% students of State Junior High Schools in Malang were at a high level of emotional intelligence, 61.3% students of State Junior High Schools in Malang were at the level moderate emotional intelligence, 12.8% of students are at a low level of emotional intelligence. (2) there is a significant difference between the level of emotional intelligence of students based on gender, (3) there is a significant difference in the level of emotional intelligence of students from the grade level